1836 Ind. Acts 77, An Act to Prevent Disasters on Steam Boats, § 7 - (:unkn) unknown (General Publisher, 1836)
Required gun powder to be transported upon steam boats stowed away as great a distance as possible from the furnace. Written notification shall be posted in three places. In the event of loss of property or life from the powder, the owner shall be liable.
--
Keywords: GUN POWDER TRANSPORTATION